Investigating the Anti-Inflammatory Potential of Ethanol Extracts from Purple Chrysanthemum Flowers - Gilbert Samuel Sumakul; Fatimawali Fatimawali; Widdhi Bodhi; Fona Hermina Dwiana Budiarso; Billy Johnson Kepel; Aaltje Manampiring (Grimsa Journal of Science Engineering and Technology, 2025)
Indonesia has high biodiversity, with around 9,600 species of flora possessing medicinal properties. One such plant is the purple chrysanthemum (Chrysanthemum morifolium), which is rich in bioactive compounds with anti-inflammatory potential. The purple chrysanthemum is used in traditional medicine to treat various diseases and has demonstrated significant anti-inflammatory activity in vitro. Given the high prevalence of inflammatory diseases in Indonesia and the side effects associated with conventional drugs, this plant is considered a promising alternative therapy that may be safer and more effective. The aim of this study was to identify the phytochemical compounds and evaluate the anti-inflammatory activity of an ethanol extract from purple chrysanthemum flowers (Chrysanthemum morifolium) in vitro. The extract was prepared using 96% ethanol, and its anti-inflammatory activity was assessed using the red blood cell membrane stabilization method. Blood samples were collected from Wistar rats. The inhibitory concentration (IC50) values of the extract and Diclofenac Sodium were 203.08 ppm and 224.04 ppm, respectively. These findings indicate that the ethanol extract of purple chrysanthemums exhibits anti-inflammatory activity